Mothers' antenatal care visits in Padang lawas regency: A qualitative investigation - Yessy Ariescha, Putri Ayu; Machmud, Rizanda; Ocviyanti, Dwiana; Syah, Nur Afrainin; Yusrawati, Yusrawati; Bachtiar, Adang; Chatra, Emeraldy; Yani, Finny Fitry (Science Midwifery, 2025)
Pregnant women should pay close attention to their health and the health of their fetuses. To prevent maternal and infant mortality, antenatal care visits are one of the actions that must be adhered to by pregnant women. This study aims to explore the perspectives of pregnant women in antenatal care visits in Padang Lawas Regency. The study was qualitative with a grounded theory approach. This study involved five mothers using purposive sampling. Data was collected through in-depth interviews and analyzed by content analysis. The results emerged namely: 1) support from husband and family, 2) accessibility, 3) health providers, and 4) mother’s behavior. Health providers play a very important role in making antenatal care visits a success routinely and completely.